Creative teacher's dictionary: Enhancing teacher competence in creating learning media to support Indonesia's SDGs program - Dea Febrina Irawan; Adilla Dzakiroh; Diva Ayu Putri Pradana; Dwi Antika Andi Saputri; Faisal Sadam Murron (Inovasi Kurikulum, 2024)
This research focuses on the Creative Teacher's Dictionary, specially designed for educators to assist in developing digital learning media that support Indonesia's Sustainable Development Goals (SDGs) program. This dictionary is crucial in shaping high-quality educators capable of providing meaningful learning experiences. The research is guided by selecting a dictionary as the primary tool for developing educational media because a dictionary plays a strategic role in providing comprehensive guidance to educators in designing learning media that support SDGs. The Creative Teacher's Dictionary offers practical guidance on using various up-to-date applications and technologies to create innovative and relevant learning experiences. This research aims to develop the Creative Teacher's Dictionary, provide comprehensive resources for educators, and ensure the quality of its content. The research employs the Design and Development (D&D) method using the ADDIE model. The assessment involves expert validation and interviews to ensure the quality of the content of the Creative Teacher's Dictionary. The validation results by subject matter experts and language experts indicate an "Very Good" assessment. The final trial results affirm that this book can enhance teachers' competence in creating learning media and can be used by educators and students needing the most up-to-date information. This research analyzes the implementation, evaluates strengths and weaknesses, and provides solutions for creating learning media based on relevant application categories.   Abstrak Penelitian ini membahas tentang Kamus Guru Kreatif yang dirancang khusus untuk para pendidik, membantu pengembangan media pembelajaran berbasis digital yang mendukung program Sustainable Development Goals (SDGs) Indonesia. Kamus ini berperan membentuk pendidik berkualitas yang mampu memberikan pengalaman belajar bermakna. Penelitian ini dipandu oleh pemilihan kamus sebagai alat utama pengembangan media pembelajaran karena kamus memiliki peran strategis dalam memberikan panduan lengkap bagi pendidik dalam merancang media pembelajaran yang mendukung SDGs. Kamus Guru Kreatif menyediakan panduan praktis tentang penggunaan berbagai aplikasi dan teknologi terkini untuk menciptakan pengalaman pembelajaran yang inovatif dan relevan. Tujuan dari penelitian ini adalah mengembangkan Kamus Guru Kreatif, menyediakan sumber daya yang komprehensif bagi pendidik, dan menjamin kualitas isinya. Penelitian ini menggunakan metode Design and Development (D&D) dengan model ADDIE. penilaian ini melibatkan validasi ahli dan wawancara untuk memastikan kualitas konten Kamus Guru Kreatif. Hasil validasi ahli materi dan ahli bahasa menunjukkan penilaian pada kategori “Sangat Baik”. Hasil akhir uji coba menyatakan bahwa buku ini mampu meningkatkan kompetensi guru dalam membuat media pembelajaran dan dapat digunakan oleh pendidik dan siswa yang membutuhkan sumber informasi terkini. Penelitian ini menganalisis penerapan, evaluasi kelebihan dan kelemahan, serta solusi pembuatan media pembelajaran berdasarkan kategori aplikasi yang relevan. Kata Kunci: Kamus guru kreatif; kompetensi guru; media pembelajaran; program SDGs Indonesia